The Perception of Dental Appearance Among adults - Shenoy, Priyanka; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The perception of beauty may be influenced by cultural, ethnic, or racial concepts of beauty. When planning treatment for aesthetics, the design of the smile cannot be isolated from a comprehensive approach to patient care. Achieving a successful, healthy, and functional result requires an understanding of the interrelationship among all the supporting oral structure. The knowledge and understanding of a patient’s perception of dental appearance is an important aspect of patient management that can help dentists in the planning of treatment that is acceptable to the patient and achieving the highest level of patient satisfaction. Aim: The aim of this study was to investigate the aspects related to the perception of dental appearance and expectations of patients who receive dental treatment in graduation clinics of Saveetha Dental College. Methodology: The survey was conducted using a questionnaire. It was evaluated 100 patients of both genders aged over 18. The questionnaire included questions of demographic data, questions to assess facial and dental aesthetics, dental satisfaction and treatments considering patients notion to improve dental esthetics. The data collected was analyzed using descriptive statistics. Results: The factor teeth for facial analysis and factor positioning in the arch for smile analysis were considered the most important subjects regarding the esthetic according to the respondents. (70%) of patients were dissatisfied with the appearance of their teeth, and dissatisfaction with the color was the most important factor. The treatment most desired was tooth whitening and (60%) of patients said yes to it. Conclusion: Respondents place great value on the teeth on the face appearance, and it can be seen that aesthetic treatments are highly valued in all age groups. There is a need for treatments to restore the function, but treatments to improve dental appearance were the most requested.